Maternal hypertension and feto-placental growth restriction is reversed by sildenafil: Evidence of independent effects of circulating nitric oxide levels - Gonçalves-Rizzi, Victor Hugo [UNESP] (2018)
Sildenafil has shown nitric oxide (NO)-independent pleiotropic effects, however the mechanisms involved are unclear. We investigated the protective effects of sildenafil against hypertension in pregnancy and feto-placental growth restriction induced by NO inhibition, and if sodium nitrite-derived NO formation influences sildenafil effects. We evaluated the plasmatic levels of NO metabolites, cyclic guanosine monophosphate (cGMP), oxidative stress and myeloperoxidase, which are involved in endothelial dysfunction during hypertension in pregnancy. Also, we performed in vitro experiments to examine cell viability and NO synthesis in human umbilical vein endothelial cells (HUVECs) cultures incubated with plasma from healthy or hypertensive pregnant rats treated (or not) with both drugs, either alone or in association. Sildenafil blunted hypertension in pregnancy and protected against feto-placental growth restriction induced by NO inhibition and these effects of sildenafil alone were similar to those presented by its association with sodium nitrite. Protective effects of sildenafil were observed even with low plasmatic NO levels and were not followed by increases in cGMP levels. Also, sildenafil, but not sodium nitrite, blunted the increases in myeloperoxidase activity. Both drugs (isolated or in association) presented antioxidant effects. Plasma from hypertensive pregnant rats treated with sildenafil, but not sodium nitrite alone, increased the viability of HUVECs. NO synthesis in HUVECs cultures was increased with plasma from rats treated with both drugs. We conclude that sildenafil effects are not dependent of circulating NO levels in hypertension and feto-placental growth restriction. These findings may reflect a protection against myeloperoxidase and pro-oxidant activation in hypertension in pregnancy.